Having Our “Omic” Cake and Eating It Too?: Evaluating User Response to Using Blockchain Technology for Private and Secure Health Data Management and Sharing - Lemieux, Victoria L.; Hofman, Darra; Hamouda, Hoda; Batista, Danielle; Kaur, Ravneet; Pan, Wen; Costanzo, Ian; Regier, Dean; Pollard, Samantha; Weymann, Deirdre; Fraser, Rob (Frontiers in Blockchain, 2021)
This paper reports on end users’ perspectives on the use of a blockchain solution for private and secure individual “omics” health data management and sharing. This solution is one output of a multidisciplinary project investigating the social, data and technical issues surrounding application of blockchain technology in the context of personalized healthcare research. The project studies potential ethical, legal, social and cognitive constraints of self-sovereign healthcare data management and sharing, and whether such constraints can be addressed through careful user interface design of a blockchain solution.